Strategies for the treatment of acute myeloid leukemia with FLT3 mutations: a patent review - Gorecki, Lukas; Reznickova, Eva; Krystof, Vladimir; Rezacova, Martina; Ceckova, Martina; Korabecny, Jan (Expert opinion on therapeutic patents, 2025)
INTRODUCTION: Approximately one-third of all AML patients have a mutation in the Fms-like tyrosine kinase 3 (FLT3) gene, which is associated with a poor prognosis in these individuals. The 2017 approval of midostaurin, the first FLT3 inhibitor, spurred extensive development of more potent and selective inhibitors with an improved safety profile. AREAS COVERED: This review analyzes patent inventions for the treatment of AML using FLT3 inhibitors, covering developments from the earliest to the most recent, disclosed in 2024. Our search using the global Espacenet database identified numerous compounds with low nanomolar inhibitory concentrations against FLT3-ITD and FLT3-TKD mutants. These compounds have shown promise in preclinical studies. Co-inhibition strategies and combinatorial therapies to overcome resistance and enhance anti-leukemic efficacy are also discussed. EXPERT OPINION: Recent patents highlight advances in the field of FLT3 inhibitors with a focus on overcoming resistance, improving selectivity and potency. Future strategies may include third-generation inhibitors such as type III allosteric inhibitors, irreversible inhibitors, or PROTACs. Personalized medicine approaches utilizing genetic profiling to tailor therapies are emphasized. Exploration of novel combination regimens with emerging therapies like CAR T-cell therapy, immune checkpoint inhibitors, and small molecules targeting critical AML pathways is ongoing to further enhance anti-leukemic efficacy.
Keywords: mutace; patenty jako téma; Animals; individualizovaná medicína; Drug Resistance, Neoplasm; inhibitory proteinkinas; Fms-like tyrosine kinase 3; Staurosporine; Drug Development; anticancer drug discovery; vyvíjení léků; lidé; Antineoplastic Agents; protinádorové látky; chemorezistence; Mutation; prognóza; staurosporin; Protein Kinase Inhibitors; tyrosinkinasa 3 podobná fms; akutní myeloidní leukemie; Prognosis; Acute myeloid leukemia; patent review; Patents as Topic; fms-Like Tyrosine Kinase 3; Precision Medicine; zvířata; FLT3 mutation; Leukemia, Myeloid, Acute; Humans